A DNA end-binding factor involved in double-strand break repair and V(D)J recombination. - Rathmell, W K (1994)
We have identified a nuclear factor that binds to double-stranded DNA ends, independently of the structure of the ends. It had equivalent affinities for DNA ends created by sonication or by restriction enzymes leaving 5', 3', or blunt ends but had no detectable affinity for single-stranded DNA ends. Since X rays induce DNA double-strand breaks, extracts from several complementation groups of X-ray-sensitive mammalian cells were tested for this DNA end-binding (DEB) activity. DEB activity was deficient in three independently derived cell lines from complementation group 5. Furthermore, when the cell lines reverted to X-ray resistance, expression of the DEB factor was restored to normal levels. Previous studies had shown that group 5 cells are defective for both double-strand break repair and V(D)J recombination. The residual V(D)J recombination activity in these cells produces abnormally large deletions at the sites of DNA joining (F. Pergola, M. Z. Zdzienicka, and M. R. Lieber, Mol. Cell. Biol. 13:3464-3471, 1993, and G. Taccioli, G. Rathbun, E. Oltz, T. Stamato, P. Jeggo, and F. Alt, Science 260:207-210, 1993), consistent with deficiency of a factor that protects DNA ends from degradation. Therefore, DEB factor may be involved in a biochemical pathway common to both double-strand break repair and V(D)J recombination.